A Corpus-Based Study of Semantic Categorizations of Attracted Adjectives to the it BE ADJ clause Construction. (April 2022) - Wang, Jiaojiao; Zhou, Jiangping
By implementing such corpus approaches as collexeme analysis and hierarchical cluster analysis, this paper investigates the semantic categorizations of adjectives that are extremely significantly attracted to the it BE ADJ clause construction in English. The findings demonstrate that these adjectives could be at least subdivided into seven different semantic clusters that denote (1) importance, necessity, and possibility; (2) appropriateness, reasonability, and unreality; (3) impracticability and irrelevance; (4) undeniability and axiomaticity; (5) obviousness; (6) dubiety, desirability, and ease; (7) improbability and anomalousness.